EXCELLENT PROGRAM IN MADRASAH ALIYAH DARUL HUDA MAYAK TONATAN PONOROGO - Nurul Fatqurrahman; Zaenal Abidin (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2018)
This excellent program is one of the school's efforts to improve the quality of education. Schools have an important role in improving quality based on innovation and creative school management that is dynamic, energetic and full of ideas. Schools have an important role in producing quality and competitive graduates. Which is able to be competitive in the process of academic and non-academic education so as to realize students who excel.Madrasah Aliyah Darul Huda Mayak Tonatan Ponorogo organizes education with the aim of producing superior graduates. In order to produce graduates who excel it is demanded that the teaching-learning process excel also organizes madrasa programs which are commonly called superior programs. Thus the special class program embodies this goal. Because Madrasah Aliyah Darul Huda Mayak Tonatan Ponorogo is one of the schools that succeeded in developing special class programs both in the field of da'wah, recitation, or the art of calligraphy and hadroh. The formulation of the problems in this study are, How to model superior programs in Madulah Aliyah Darul Huda Ponorogo Academic Year 2018/2019, and How to implement flagship programs in Madrasa Aliyah Ponorogo 2018/2019 Academic Year. The aim is to find out and describe: 1) The model of the flagship program in Madrasah Aliyah Darul Huda Mayak Tonatan Ponorogo 2018/2019 Academic Year. 2) Implementation of the flagship program in Madrasah Aliyah Darul Huda Mayak Tonatan Ponorogo Academic Year 2018/2019.This type of research is qualitative research. Data collection methods using interviews, observation, and documentation. Data analysis uses descriptive analysis, with the drawing conclusions using the deductive method that departs from general events and then reduced to specific sections. The results of this study are: First, in an effort to improve the quality of students of Madrasah Aliyah Darul Huda Mayak Tonatan Ponorogo provides a program of activities to meet the personal development needs of students both to explore interests or to optimize interests and talents. The superior program model in Madrasah Aliyah Darul Huda Mayak Tonatan Ponorogo is the realization of a special class program. School's efforts in developing and facilitating students to develop their potential through the madrasa program. Some of the leading programs in Madrasah Aliyah Darul Huda Mayak Tonatan Ponorogo include. The first is the green card program, the second is the Lughoh program, the third is the Muhadhoroh program and the last is the talent development class program (calligraphic and binary hadroh). Secondly, the implementation of the flagship program in Madulite Aliyah Darul Huda Mayak Tonatan Ponorogo has good implications, supported and well received by madrasa residents, especially for students of Madrasah Aliyah Darul Huda Mayak Tonatan Ponorogo as a program target. Evidenced by the achievement of targets in each program. For the Green Card program, which is implemented every madrasah semester, the KKM has been set on the green card assessment standard. Both of the Lughoh Program, the main activity of this program is the addition of basic Arabic and English language materials which are implemented a day after the KBM begins. The Third Muhadhoroh Program is an activity to develop students' intellectual preaching and develop the ability to make 4 language speeches, which are held twice a month. The fourth class is developing calligraphy and hadroh talents. Both of these programs become icons for madrassas so that they are widely known by the wider community of Ponorogo through their achievements. Both achievements achieved at the provincial and national level